Ethnobotanical Study and Conservation Status of Medicinal Plants Used by Local Community in Desa Namo Bintang, North Sumatra - Mariah Ulfa; Harisyah Manurung; Chetyfani Aquilera br. Ginting; Dita Sari Prabuningrum (Talenta Publisher, 2026)
The indigenous communities in North Sumatra exhibit unique languages, rituals, traditional dwellings, and profound cultural heritages, encompassing indigenous knowledge of medicinal botany. Modernization, apathy and lifestyle changes among younger generations have put this traditional knowledge in risk of extinction due to its oral transmission throughout generations. Therefore, this study aims to capture the traditional knowledge by ethnobotanical surveys in Desa Namo Bintang for the preservation of potentially vital details. The number of respondents in this study was determined using the Slovin formula with a 10% margin of error. Data collection was conducted by interviewing 97 respondents selected using purposive sampling. The ethnobotanical data recorded were the scientific and vernacular names of medicinal plants, growth form, family, plant part used, preparation methods, medicinal benefits/types of diseases that can be treated, number of plant individuals, conservation status and documentation. The conservation status was obtained from the website of IUCN Red List. This study identified 85 species of medicinal plants in Desa Namo Bintang, classified into 37 families. The predominant medicinal herb utilized by respondents was Zingiber officinale, Cymbopogon citratus, Curcuma longa, Kaempferia galanga, and Curcuma xanthorrhiza. The family Zingiberaceae represented the greatest number of species. Leaves were the most commonly employed ingredient, and the main preparation method was decoction. The evaluated medicinal plants were mostly categorized as Least Concern (LC), while one species, Swietenia mahagoni, was classified as Near Threatened (NT). The necessity for local conservation depends on both the intensity of community use and the sustainability of harvesting practices. The current study proposes community-based conservation by developing cultivation plots and implementing sustainable harvesting.